The Neurobiology of Imagination: Possible Role of Interaction-Dominant Dynamics and Default Mode Network - Agnati, Luigi F.; Guidolin, Diego; Battistin, Leontino; Pagnoni, Giuseppe; Fuxe, Kjell (Frontiers in Psychology, 2013)
This work aims at presenting some hypotheses about the potential neurobiological substrate of imagery and imagination. For the present purposes, we will define imagery as the production of mental images associated with previous percepts, and imagination as the faculty of forming mental images of a novel character relating to something that has never been actually experienced by the subject but at a great extent emerges from his inner world. The two processes appear intimately related and imagery can arguably be considered as one of the main components of imagination. In this proposal, we argue that exaptation and redeployment, two basic concepts capturing important aspects of the evolution of biological structures and functions (Anderson, 2007), could also be useful in explaining imagery and imagination. As far as imagery is concerned it is proposed that neural structures originally implicated in performing certain functions, e.g., motor actions, can be reused for the imagery of the virtual execution of that function. As far as imagination is concerned we speculate that it can be the result of a “tinkering” that combines and modifies stored perceptual information and concepts leading to the creation of novel “mental objects” that are shaped by the subject peculiar inner world. Hence it is related to his self-awareness. The neurobiological substrate of the tinkering process could be found in a hierarchical model of the brain characterized by a multiplicity of functional modules (FMs) that can be assembled according to different spatial and temporal scales. Thus, it is surmised that a possible mechanism for the emergence of imagination could be represented by modulatory mechanisms controlling the perviousness of “modifiers” along the communication channels within and between FMs leading to their dynamically reassembling into novel configurations.